Protein Mutation Effect Prediction via Graph-Based Modeling of Residue pKa Shifts and Local Electrostatic Rewiring - Leon Satkings; Lummy Lawrence (International Journal of Clinical and Translational Medicine, 2026)
Predicting the functional and stability consequences of amino acid substitutions remains a cornerstone challenge in computational biology, with far-reaching implications for precision medicine, protein engineering, and the interpretation of genomic variation. While significant progress has been made by leveraging evolutionary sequence conservation and global structural features, the nuanced role of localized electrostatic perturbations, particularly those arising from residue-specific pKa shifts, has been comparatively underexplored in large-scale mutation effect prediction systems. This paper presents an interdisciplinary perspective on the design, deployment, and governance of graph-based modeling frameworks that explicitly encode pKa value alterations and the resultant electrostatic rewiring at protein interfaces. We articulate a system-level architecture in which proteins are represented as heterogeneous graphs with ionizable residues as charge-carrying nodes, and where edge attributes capture coulombic coupling and solvent exposure. By integrating physically inspired feature engineering with message-passing neural networks, such a system can capture the propagation of local charge disruptions across the contact network. The discussion extends beyond algorithmic design to address critical infrastructure demands, data provenance, robustness under distribution shift, fairness across protein families and human populations, model interpretability, and the policy frameworks required for clinical translation. We explore structural trade-offs between model granularity and computational tractability, the sustainability of training pipelines, and the ethical dimensions of embedding biophysical models into decision-support infrastructures. The analysis underscores that the value of such predictive platforms lies not solely in accuracy metrics but in the capacity to yield mechanistically transparent and socially accountable insights for variant interpretation at scale.